2014
DOI: 10.1007/s15010-014-0604-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic variants in the IRGM gene and tuberculosis in a Korean population

Abstract: This is the first study to identify a significant association between the IRGM single-nucleotide polymorphism (SNP) rs10065172 and susceptibility to active TB disease in an Asian population. The results suggest that IRGM genetic variants could be associated with susceptibility to active TB disease in the Korean population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…In the same Ghanaian population, this allele was not associated with protection from TB caused by M. africanum or M. bovis . Several other studies variously identified associations of polymorphic IRGM alleles with protection or susceptibility to TB in African-American, Iranian, Chinese and Korean populations [191-194]. In some cases opposing effects on TB susceptibility were associated with the same allele in different populations.…”
Section: Autophagy In Tbmentioning
confidence: 99%
“…In the same Ghanaian population, this allele was not associated with protection from TB caused by M. africanum or M. bovis . Several other studies variously identified associations of polymorphic IRGM alleles with protection or susceptibility to TB in African-American, Iranian, Chinese and Korean populations [191-194]. In some cases opposing effects on TB susceptibility were associated with the same allele in different populations.…”
Section: Autophagy In Tbmentioning
confidence: 99%
“…IRGM resists to the intracellular bacterium as a member of the GTPases family (Kim et al, ). Recent studies have shown that IRGM is mainly associated with chronic infectious diseases or inflammatory bowel diseases (Song et al, ; Iida et al, ). Importantly, IRGM can promote tumorigenesis and cell growth in melanoma and hepatocellular carcinoma (Dong et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The human population polymorphisms in IRGM have been linked to autophagy (Consortium, 2007; Craddock et al, 2010) and to its effector outputs including direct antimicrobial defense (Brest et al, 2011; McCarroll et al, 2008). In keeping with its autophagy-mediated antimicrobial role, IRGM is additionally a genetic risk factor for tuberculosis in different human populations (Intemann et al, 2009; Song et al, 2014) and may afford protection in leprosy (Yang et al, 2014). However, the molecular mechanism of IRGM’s function in autophagy has remained a mystery.…”
Section: Introductionmentioning
confidence: 99%